STUDY ON MICROFINANCE AND SELF-HELP GROUPS EFFECT ON WOMEN’S EMPOWERMENT IN MEHSANA DISTRICT - Prajapati, Hiteshbhai Dhanabhai; Pawar, Hukmaram D. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Rural area of the India is the real India and also rural development is the real development of the India. SHGs is a small economically parallel alliance group of the rural poor voluntarily coming to gather to small amount of money regularly which deposited in a common fund to face members needs and to provide security free loan decided the group the study aimed to analysis the reason for joining SHGs and all woman who member in SHGs them financial condition before and after join SHGs for the analysis primary data collected 100 woman who member of SHGs more than one year of Mehsana district Gujarat